Proceedings of the Mizoram Science Congress 2018 (MSC 2018) - Perspective and Trends in the Development of Science Education An 2018
DOI: 10.2991/msc-18.2018.26
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative analysis of phytochemicals of crude extracts of Ageratum conyzoides L. leaves

Abstract: Ageratum conyzoides L., belonging to the family Asteraceae, is an annual herbaceous plant and is an invasive weed. It contains bioactive compounds that are reported to possess therapeutic properties. The species has been studied widely owing to its biological properties and its potential application in medicine and agriculture. It is used in the treatment of burns and wounds, arthrosis, malaria, asthma, leprosy and dermatitis. It also has insecticidal activity against a range of major pests of field crops. Chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The earlier research work carried out by Puro et al [17] reported that the phytochemicals present in the aqueous leaf extract of Ageratum conyzoides highly influence the antimicrobial activity, which is in line with the present study. Many research studies have suggested that the plant variety of Ageratum species is found to have excellent biological properties, as it is reported to have various phytochemicals, such as phenols, bromophenols, polysaccharides, tannins, flavonoids, phenolic acids and carotenoids [13][14][15][16]18,19].…”
Section: Discussionsupporting
confidence: 93%
“…The earlier research work carried out by Puro et al [17] reported that the phytochemicals present in the aqueous leaf extract of Ageratum conyzoides highly influence the antimicrobial activity, which is in line with the present study. Many research studies have suggested that the plant variety of Ageratum species is found to have excellent biological properties, as it is reported to have various phytochemicals, such as phenols, bromophenols, polysaccharides, tannins, flavonoids, phenolic acids and carotenoids [13][14][15][16]18,19].…”
Section: Discussionsupporting
confidence: 93%
“…Arya et al (2011) andVasantharani et al (2022) reported various biological properties, such as antifungal, cytotoxic, nematicidal, antifeedant and larvicidal activities. These occurring activities could be related to the presence of various phytochemicals, such as bromophenols, polysaccharides, tannins, flavonoids, phenols, phenolic acids and carotenoids (Chandraker et al, 2019;Puro et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The aim is to highlight the bioactive phytochemical groups involved in the insecticidal activities observed. Quantitative analysis was performed following the standard procedure for phenols (Ainsworth and Gillespie, 2007), flavonoids (Chang et al, 2002) and alkaloids (Puro et al, 2018).…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…Medicinal plants and human beings have special relationship for centuries [11][12][13]. Medicinal plants and natural products having pharmacological models have been well thought out as alternative therapy for the treatment of various diseases [14][15][16]. A significant number of presently used antimalarial, antioxidant, anthelminthic, anti-inflammatory, and antitumor agents are molecules identified and isolated from plants or their synthetic or semisynthetic derivatives [17][18][19].…”
Section: Introductionmentioning
confidence: 99%